2001
DOI: 10.1098/rspb.2001.1653
|View full text |Cite
|
Sign up to set email alerts
|

Separating the effects of predation risk and interrupted foraging upon mass changes in the blue titParus caeruleus

Abstract: The optimal amount of reserves that a small bird should carry depends upon a number of factors, including the availability of food and environmental predation risk levels. Theory predicts that, if predation risk increases, then a bird should maintain a lower level of reserves. Previous experiments have given mixed results: some have shown reduced reserves and some, increased reserves. However, the birds in these studies may have been interpreting a staged predation event as a period when they were unable to fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 43 publications
4
29
0
1
Order By: Relevance
“…For example, Rands & Cuthill (2001) found that the mean reserves of blue tits during June and July increased in response to interruptions but decreased in response to simulated predation. Our model shows that encounters with predators can decrease mean reserves, but it can also produce a greater increase than expected from an interruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Rands & Cuthill (2001) found that the mean reserves of blue tits during June and July increased in response to interruptions but decreased in response to simulated predation. Our model shows that encounters with predators can decrease mean reserves, but it can also produce a greater increase than expected from an interruption.…”
Section: Discussionmentioning
confidence: 99%
“…Models predict that increasing the frequency of interruptions should increase optimal levels of fat (e.g. Houston & McNamara 1993), so it has been suggested that presenting a bird with a model of a predator might increase its fat reserves (Lilliendahl 1998;Pravosudov & Grubb 1998;van der Veen & Sivars 2000;Gentle & Gosler 2001;Rands & Cuthill 2001). There are two problems with viewing the presence of a predator as just an interruption.…”
Section: Introductionmentioning
confidence: 99%
“…v www.esajournals.org stimulate the bird to increase fat reserves in the newly unpredictable foraging environment (McNamara et al 1994, Rands andCuthill 2001). Fat has increased in response to measures of increased predation risk (Fransson and Weber 1997, Lilliendahl 1998, Pravosudov and Grubb 1998, Bautista and Lane 2000.…”
Section: Background Theorymentioning
confidence: 99%
“…Two main methods are used: a) if the bird is captured and handled directly, the bird is bagged and weighed on a scale. This method can stress the bird and cause body mass reduction in a short time (Rands & Cuthill, 2001), a fact that should be taken into account when analysing data. b) When we do not wish to capture the bird, attracting it to a place situated on a scale which automatically records mass variation will suffice.…”
Section: What Measures Should Be Taken Into Accountmentioning
confidence: 99%